DANTHONIA DECUMBENS (DANTHONIAE, POACEAE), NUEVA ESPECIE ADVENTICIA PARA LA FLORA DE CHILE CONTINENTAL - Rúgolo de Agrasar, Zulma E.; García, Nicolás; Mieres, Gustavo (Gayana Botánica, 2009)
This article reports the finding of Danthonia decumbens (L.) DC. in the surrounding of Puerto Montt (41º26’ S; 73º05’ W) in the south of Chile, which also constitutes the first register of this European grass in South America.